MOTHER-BABY BONDING: ENHANCING EMOTIONAL CONNECTIONS VIA SPECIALIZED TRAINING - Fatima , Mahmoud Hassan El-Azab; Ahmed , Abdel-Hamid Ali (Research Journal of Health, Medicine and Nursing, 2024)
Attachment during pregnancy is a vital component of maternal-fetal bonding, influencing the long-term development of both the mother and the unborn child. This emotional connection, beginning before conception and continuing throughout pregnancy, profoundly impacts the physical, emotional, and cognitive well-being of the infant. Maternal-fetal attachment is characterized by various maternal behaviors that reflect the emotional bond with the fetus. These behaviors encompass aspects of self-care such as proper nutrition, adequate sleep, and physical exercise, as well as abstaining from harmful substances like alcohol and drugs. Furthermore, maternal-fetal attachment fosters the mother's desire to connect with and understand her unborn child. This emotional connection is not only instrumental in ensuring a favorable pregnancy outcome but also in promoting the health of both mother and neonate. In this paper, we explore the significance of maternal-fetal attachment and its multifaceted role in prenatal care.